A Method for Harmonic Power Tracing by Using Upstream and Downstream Distribution Matrices. Issue 13 (9th August 2019) - Narimani, Mahmood; Hosseinian, Seyed Hossein; Vahidi, Behrooz
Abstract: In this paper, an algorithm to find the harmonic power flow path for every generator and demand is proposed. In the proposed algorithm, the exact knowledge of harmonic power values is not required to determine the path. Our approach is based on Bialek's tracing method, which specifies the contribution of each nodal generation/demand in power flow of a particular line. Our approach is faster than Bialek's method in terms of computation due to the fact that upstream and downstream distribution matrices as well as nodal demand and generation matrices have a much simpler structure. Our method resolves electricity tracing for harmonic problems in both upstream and downstream aspects, resulting in two sets of answers: one for the harmonic power flow path of generator nodes and the other for that of demand nodes. To illustrate our algorithm, a step-by-step solution to a sample case study is provided here using the proposed algorithm. To verify our method, the results of our algorithm for a sample 5-bus power network and the IEEE 14-bus test system are compared to those of Bialek's method. Finally, the proposed method is applied for harmonic frequency and used to find the path of harmonic power flow in a network.